Cholesterosic polyposis of gallbladder. - Estapé, Gonzalo; Olivera, Daniel; de los Santos, Julio; Falconi, Luis (Cirugía del Uruguay, 1976)
This is a case of polypoid gallbladder cholesterosis in a man aged 53, with case history including hypostenic dyspepsia and pain of right upper quadrant of the abdomen. Radiology showed a polipoid formation in gallbladder. Cholecystectomy was performed and revealed the existence of strawberry gallpladder with considerably developed cholesterosic pseudopolyps in the mucose membrane. Postoperatory evolution was asymptomatic .